Grouting in rock cavern : a case study - Lim, Kan Xuan (2017)
In current context, most of the civil and mining engineering projects use grouting as an aid for gound improvement. As such, when considering in grouting operations, the groutability and grout penetration depth are important issues to be looked at. Various parameters such as joint system, geomechanical characteristics, grout properties and technical factors such as grouting pressure affect the groutability and grout penetration depth in a jointed rock mass. In order to give a better prediction of grouting results, having sufficient knowledge of the effect of these parameters are important. In this study the effect of important parameters on grouting process in a jointed rock mass of Jurong Rock Cavern.are studied The analyses will focus on two key parameters which are Q-values and RMR values. Results can be used as a guide for grouting analysis in future similar underground tunnelling projects. With the numerical data gathered from Jurong Rock Cavern, the author aims to identify relationship between the grouting volume used with the rock parameters.